Strategi Pengembangan Kepemimpinan melalui Pelatihan dan Pengembangan Karir - Waruwu, lisma; Rahayu, Enik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the effectiveness of the leadership training program at LPK Kartika and its impact on the development of leadership skills and career planning of participants. This study employs a qualitative approach with an exploratory case study method to gain a deeper understanding of the leadership development strategies implemented. The research informants consisted of training participants, instructors, and LPK management who were selected purposively. Data were collected through in-depth interviews, direct observation, and document analysis, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion. The study's results indicate that interactive methods, such as group discussions, case studies, and simulations, are effective in enhancing participants' communication skills, teamwork, and decision-making abilities. Mentoring strategies and leadership projects have also been shown to help participants plan their careers more focused. The findings also recommend extending the duration of training and strengthening the mentoring system as well as integrating digital technology to improve the long-term effectiveness of training.